ORGANIKALÍQ TÓGINLERDI LOKAL SALATUǴÍN QURÍLMANÍŃ DISKLI QARÍQ ASHQÍSHTÍŃ TIKKE SALÍSTÍRǴANDA ORNATÍLÍW MÚYESHINIŃ OLARDÍŃ JUMÍS KÓRSETKISHLERINE TÁSIRI - Ibragimov, A.A.; Ramazanov, B.B.; Ramazanov, B.N. (SCIENCE and SOCIETY, 2025)
According to the results of the research conducted in this article, the study aims to justify the optimal parameters of the installation angle of disc furrow openers relative to the direction of movement to form the required furrow with minimal energy consumption.